Facies and Depositional Environment Analysis of Limestone in Citeureup Area, West Java, Indonesia - Andriansyah, Rian; Syaputra, Rizky; Robbani, Nur Ikhsan; Tabri, Kristian Nurwedi (BRIN Publishing, 2024)
The Citeureup area in West Java Province hosts Middle Miocene limestone outcrops belonging to the Klapanunggal Formation, which has long been considered a promising source of raw material for Indonesia’s cement industry. Despite its economic significance, detailed sedimentological studies and facies characterization of this formation remain limited. This study aims to identify the dominant lithofacies and reconstruct depositional environments to understand the formation’s genesis and assess its resource potential. Thin-section petrographic analysis, enhanced with blue epoxy resin, was employed to identify porosity, fossil assemblages, and mineral composition. The investigation revealed three primary facies types: packstone, boundstone, and dolomitic grainstone. The packstone and dolomitic grainstone facies are interpreted to have formed in reef-flat settings, associated with shallow, high-energy marine conditions. The boundstone facies, in contrast, are linked to reef-crest environments subjected to more dynamic hydrodynamic regimes. These findings point to a depositional system characteristic of a carbonate platform shaped by variable energy conditions. The presence of abundant skeletal grains, well-developed porosity, and mature mineralogical features indicates the limestone’s high potential as a quality raw material for cement production. Beyond its industrial relevance, the study enhances sedimentological insights into the Klapanunggal Formation and provides a scientific basis for informed resource evaluation and sustainable exploitation strategies in similar carbonate settings.